Dharurah and the Realization of Maqashid Sharia: Analysis of the Implementation of Islamic Legal Maxims on Emergency - Rohim, Ade Nur (Nurani, 2022)
Contemporary issues and phenomenon that occur in society experience development from time to time. References and arguments in the Qur'an and sunnah sometimes do not explain the law on the issue specifically. Excavation of the law by using qawa’id fiqhiyyah which has been formulated by the scholars is important. Especially in conditions of emergency and compulsion that require in-depth studies to establish laws on issues that provide a certain level of difficulty for humans. This study aims to review the concept of emergency in the perspective of fiqh by examining its correlation to the achievement of maqashid syariah by focusing on the application of qawa’id fiqhiyyah related to emergency. This research is a qualitative research using a literature study approach by doing literature review on Islamic legal maxim, maqashid sharia, and dharurah. The results of this study indicate that dharurah is a condition that positions humans in a condition of being forced to do something that is forbidden or to leave something that is obligatory. Islamic law provides rukhshah for the difficulties experienced by humans as a guarantee to realize maqashid syariah. Legal determination of the waivers granted is carried out by referring to the arguments of the Qur'an, sunnah and ijma' as well as by applying qawa’id fiqhiyyah related to emergencies.